Effect of Soil Condition on the Energy Distribution of Mid-Rise RC Buildings - Anıl Dindar, A. Anil; Bozer, Ali; Özkaynak, Hasan; Müderrisoğlu, Ziya; Güllü, Ahmet (Springer Science and Business Media Deutschland GmbH, 2025)
It is well known that the energy imparted into the structure is resisted by the inelastic deformation of the structural members if they are well-detailed according to ductility conditions which are stipulated in modern seismic codes. The fundamental approach for forced-based seismic design of building-type structures relies on the strength of the member required to resist demand forces. In the content of the forced-based design process, demand and capacity could easily be derived from linear elastic analysis. However, the location and propagation of the damage to the structural members could not be monitored explicitly. Moreover, earthquakes impart a considerable amount of input seismic energy into the structure and thus, it is much more realistic to consider energy as a substantial design criterion. This study aims to compare and quantify the energy dissipation characteristics of a set of 5-story reinforced concrete (RC) 3D frame-type buildings designed per the Turkish Building Earthquake Code (TBEC-2018). The buildings were designed according to five different soil conditions defined in the code. The locations are selected in high-seismic regions of Turkiye. The buildings were then chosen from the group of 250 models studied, eliminating 92 of them due to excessive lateral drift, axial load on columns, or joint-shear safety cases. According to TBEC (2018), seismic load reduction (R) and overstrength factors (D) were selected as 8 and 3, respectively. Therefore, ductile structural design principles could be ensured at the selected seismic design performance level, which enable plastic deformations to occur at the ends of the structural beam members. The energy dissipation characteristics are evaluated as ratio of energy dissipation among the stories and member types in all structural models by means of conducting lateral nonlinear static analysis. © 2025 Elsevier B.V., All rights reserved.
3rd International Workshop on Energy-Based Seismic Engineering, IWEBSE 2025 -- Istanbul -- 334289
Keywords: 3D RC frame; energy dissipation; ETABS API; Python; Turkish Building Earthquake Code